The use of herbal and dietary supplement among community-dwelling elderly in a suburban town of Malaysia - Abd Wahab, Mohd Shahezwan; Zaini, Muhammad Helmi; Ali, Aida Azlina; Sahudin, Shariza; Mehat, Muhammad Zulfadli; Abdul Hamid, Hafizah (BioMed Central, 2021)
Background The use of herbal and dietary supplement (HDS) in health and disease management has gained global attention. HDS are generally accepted by the public and are associated with positive health behaviours. However, several reports have been documented with regards to their potential adverse effects and interaction with conventional medicines. Limited data is currently available on the use of HDS among elderly population in Malaysia. This present study aims to investigate the prevalence of and pattern of HDS use among a sample of community-dwelling elderly in a suburban town in Malaysia. Methods A cross-sectional survey was conducted between March and May 2019 among the elderly aged [greater than or equai to]60 years old. The participants with the following criteria were included in the study: aged [greater than or equai to]60 years, residing in Puncak Alam and able to understand Malay or English language. Data were collected using a pre-validated questionnaire. All statistical analysis was conducted using IBM SPSS ver. 23. Results Overall, 336 out of 400 elderly responded to the survey, achieving a response rate of 84%. This study observed that almost 50% of the respondents were using at least one type of HDS in the past one month of the survey. Among HDS non-users, most of them preferred to use modern medicines (62.6%, 114/182). Among the HDS users, 75.3% (116/154) were using at least one type of modern medicine (prescription or over-the-counter medicine). Multivariate analysis showed that having good to excellent perceived health (adjusted OR = 2.666, 95% CI = 1.592-4.464), having felt sick at least once in the past one month (adjusted OR = 2.500, 95% CI = 1.426-4.383), and lower body mass index (adjusted OR = 0.937, 95% CI = 0.887-0.990) were associated with HDS use. It was noted that only a small percentage of HDS users (16.2%, 25/154) had informed healthcare providers on their HDS use. Conclusion The use of HDS is common among the elderly sampled. Hence, healthcare providers should be more vigilant in seeking information of HDS use for disease management in their elderly patients. Campaigns that provide accurate information regarding the appropriate use of HDS among the elderly are pertinent to prevent misinformation of the products.